Improvement of anti-corrosive and anti-oxidative properties of electroless Ni-P coating. (3rd October 2019) - Shan, Limei; Li, Yanli; Miao, Jingguo; Wu, Juying; Zhai, Kaihua; Wang, Xinyin
ABSTRACT: In order to improve the anti-corrosive and anti-oxidative properties of electroless Ni-P coating (ENPC), a vanadium conversion coating (VCC) was fabricated on the surface of the ENPC. SEM images and EDX line scanning spectra indicate that as-prepared VCC is supposed to be a thin film with a thickness of a few nanometres. XPS analyses demonstrate that the VCC is mainly consisted of V2 O5 or V2 O5 · n H2 O. The acid exposure test data indicate that the VCC-treated ENPC, compared with the pristine one, demonstrates a highly enhanced anti-oxidative property. Furthermore, the result of neutral salt spray test manifests that the VCC-treated ENPC has also a highly enhanced anti-corrosive property, which is further confirmed by the result of electrochemical corrosion test.